2012
DOI: 10.1186/1752-0509-6-152
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying off-target effects for torcetrapib using network pharmacology and reverse docking approach

Abstract: BackgroundTorcetrapib, a cholesteryl ester transfer protein (CETP) inhibitor which raises high-density lipoprotein (HDL) cholesterol and reduces low-density lipoprotein (LDL) cholesterol level, has been documented to increase mortality and cardiac events associated with adverse effects. However, it is still unclear the underlying mechanisms of the off-target effects of torcetrapib.ResultsIn the present study, we developed a systems biology approach by combining a human reassembled signaling network with the pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 51 publications
(63 reference statements)
0
21
0
Order By: Relevance
“…To acquire high-quality human cancer signaling, we manually curated cancer signaling molecules thoroughly [48], [49]. All the over-represented genes obtained from the virtual RDSs were mapped to portray the context-specific sub-communities and the remodeled signaling regulatory networks were redistributed according to their subcellular localization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To acquire high-quality human cancer signaling, we manually curated cancer signaling molecules thoroughly [48], [49]. All the over-represented genes obtained from the virtual RDSs were mapped to portray the context-specific sub-communities and the remodeled signaling regulatory networks were redistributed according to their subcellular localization.…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, a map of human cancer signaling was firstly obtained from Cui et al , which united manually curated signaling molecules including BioCarta (http://www.biocarta.com/) [62], literature-mined signaling network [63], Cancer Cell Map including cancer mutated genes obtained from COSMIC database and other high-throughput profiling, methylated genes in cancer stem cells, cancer associated gene set acquired from plasmID (http://plasmid.hms.harvard.edu/) and Online Mendelian Inheritance in Man (OMIM, http://www.ncbi.nlm.nih.gov/omim). Subsequently, Human Protein Reference Database (HPRD, http://www.hprd.org/) [49] and REACTOME (http://www.reactome.org/) databases were appended. After adding connections between signaling molecules based on SysBiomics platform (http://biomine.cigb.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the off-target effects of the drug candidates are the main cause of toxicity and side effects and responsible for high attrition rate in drug development. Using reverse docking strategy, the off-targets can be predicted by identifying all possible binding proteins of the drug candidates in the host system [77].…”
Section: • Computational Drug Discovery Approachesmentioning
confidence: 99%
“…Furthermore, the obtained potential off-targets of torcetrapib were identified by employing the reverse docking strategy. The results suggested that plateletderived growth factor receptor (PDGFR), hepatocyte growth factor receptor (HGFR), interleukin-2 (IL-2) receptor, and epidermal growth factor receptor (ErbB1) tyrosine kinase were highly relevant to unfavorable adverse effects [76].…”
Section: Reviewmentioning
confidence: 99%